OPIVA Refined - A Human-Centred Approach to Outpatient Intravenous Antibiotic Treatment - Weatherly, Kate (Auckland University of Technology, 2021)
Since its inception in America during the early 1970s, outpatient intravenous antibiotic (OPIVA) therapies have provided patients with live-saving intravenous antibiotics at home rather than in hospitals (Williams et al., 2015). OPIVA services typically involve six to eight weeks of intensive antibiotic treatment following a period of inpatient care. Beyond saving money and valuable bed spaces, these therapies have allowed patients to recover from severe infections in the comfort of their own homes. However, the existing literature around these services has essentially only considered the clinical function and outcomes of the services, with little research discussing the patient’s experiences with the products that make up the treatment systems (Dodd, 2007; Zahnd et al., 1999). The existing OPIVA treatment systems comprised an elastomeric infuser, a peripherally inserted central catheter (PICC), a sterile dressing, an IV extension line, surgical tape (to manage the IV line), and a storage bag for the elastomeric infuser. Existing literature demonstrates little understanding of how the medical devices that make up the OPIVA system could be improved. In response to this gap in the literature, this research used human-centred design (HCD) methods to explore how the medical devices that make up the Waitematā District Health Board’s (Waitematā DHB) OPIVA service could be redesigned to improve the experiences of patients within the service. For many medical devices, clinical staff were the primary users. However, for OPIVA, patients must learn to manage the OPIVA treatment system themselves (or with the help of a family member or district nurse). Managing the OPIVA system involves changing the elastomeric infuser every 24 hours. In this project, primary research was conducted with previous OPIVA patients, OPIVA clinical staff and a previous patient expert user. Through the experiences and input of these participants, the research focused on improving the usability, aesthetics and ergonomics of the infuser and redesigning the storage bag to be wearable under clothing. Along with the redesign of these elements, this research proposed a new system to replace the surgical tape used to hold the IV lines in place on the patient’s arm, which could help to increase the accessibility and ease of use of the system. Participants were able to provide feedback on these concepts during expert critique sessions throughout the research, which helped inform the design process and validate the design outcomes. By exploring how patients could be more directly involved in the medical device development process, my research used Action Research and HCD methodologies to advocate for the inclusion of patients experiences in the redesign of the products that make up the OPIVA treatment system. Many medical device development processes overlooked patients as stakeholders in the design process at the time of writing. The dominant perspectives on medical product design in the past have centred on minimising production costs while maintaining the health outcomes of patients. This development process has often left patients out of the development process (Money et al., 2011; Shah & Robinson, 2007). The findings of this research demonstrated that if patients’ experiences were involved in the design process of medical devices, then the usability of those devices could be improved. This research sets a precedent for potential future design research to explore how usability for medical devices could be improved by including patients in the design process.
Keywords: Design; Product design; Human-centred design; Human centred design; HCD; Medical device; Product; Healthcare; Wellbeing; Medical; Patient centred; Patient; Reflective practice; Action research; Prototype; Industrial design; OPIVA; IV; PICC lines; Non-consumer product; Intravenous Antibiotics; Outpatient intravenous antibiotic service; OPAT; Outpatient parenteral antimicrobial therapy